An evaluation of patients with a previous endemic coronavirus infection during the COVID‐19 pandemic. Issue 7 (25th March 2021) - Otlu, Baris; Yakupogullari, Yusuf; Tanriverdi, Elif S.; Bayindir, Yasar
Abstract: Few studies exist on the clinical manifestation of coronavirus disease 2019 (COVID‐19) in patients who previously had a common cold due to an endemic coronavirus (eCoV). In a retrospective scan of the data obtained in our microbiology laboratory, 64 patients who were diagnosed with an eCoV infection between 2016 and 2020 were identified. National COVID‐19 surveillance data showed that four (6.2%) of 64 patients were infected with severe acute respiratory syndrome coronavirus 2 by the end of 2020, while, simultaneously, the COVID‐19 prevalence in the city of Malatya ranged from 7.8% (polymerase chain reaction‐based diagnosis) to 9.2% (total diagnosis). The differences were found statistically significant (6.2% vs. 7.8%, p  < .01; 6.2% vs. 9.2%, p  < .001). Patient interviews and evaluation of medical records revealed that these four patients did not manifest any severe COVID‐19 symptoms despite their substantial comorbidities, and they did not require hospitalization. Consequently, despite a low number of samples, we determined a lower frequency of COVID‐19 among the patients who had a prior eCoV infection, and the results of this study support the previous findings that people with a prior eCoV infection develop a milder case of COVID‐19. Our results may provide some insights for future studies aiming at vaccine development, but detailed investigations are still required.